Mortality from lung cancer in Ontario uranium miners. Issue 10 (October 1993) - Kusiak, R A; Ritchie, A C; Muller, J; Springer, J
Abstract : Mortality from lung cancer was greater in Ontario uranium miners than in the general male population of Ontario (observed = 152, expected = 67.6, standardised mortality ratio 225, 95% confidence interval 191-264). Part of the excess of lung cancer may be because the proportion of men who are smokers or have smoked is greater in uranium miners than in Ontario men. Smoking does not explain the whole excess. Mortality from lung cancer in Ontario uranium miners is clearly related to exposure to short lived radon progeny. The excess relative risk of lung cancer from the same degree of exposure to short lived radon progeny is greatest five to 14 years after exposure and less subsequently. It is greater in men under the age of 55 years and less in older men. Part of the excess of lung cancer mortality in Ontario uranium miners is probably also due to exposure to arsenic that occurred earlier in gold mines. In Ontario uranium miners, the lung cancer mortality from exposure to arsenic increases as the intensity of exposure to short lived radon progeny increases. This finding is consistent with the hypothesis that the risk of lung cancer from exposure to arsenic is enhanced by exposure to other carcinogens. In Ontario uranium miners, the proportion of lung cancers that are small cell carcinomas is greater than in the general population. The proportion of small cell carcinomas is especially great five to 14 years after exposure to short lived radon progeny and in men who die from lung cancer at younger ages.